2014
DOI: 10.1007/s11033-014-3464-3
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a recombinant human insulin expression vector for mammary gland-specific expression in buffalo (Bubalus bubalis) mammary epithelial cell line

Abstract: The aim of the present study was construction of mammary gland specific expression vector for high level of human insulin (hINS) expression in transgenic buffalo for therapeutic use. We have constructed mammary gland specific vector containing human insulin gene and there expression efficiency was checked into in vitro cultured buffalo mammary epithelial cells (BuMECs). Human pro-insulin coding region was isolated from human genomic DNA by intron skipping PCR primer and furin cleavage site was inserted between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Most of the plasmid vectors are from 3 kbp to 5 kbp in length. Plasmids allow inserting a sequence of DNA up to 20 kbp in length, and have been used to obtain transgenic animals (Kaushik et al 2014). The commercial vector pBC1 with a DNA of 21.6 kbp long has been also used to obtain transgenic cattle (Yang et al 2011).…”
Section: Vectors Used In the Creation Of Transgenic Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the plasmid vectors are from 3 kbp to 5 kbp in length. Plasmids allow inserting a sequence of DNA up to 20 kbp in length, and have been used to obtain transgenic animals (Kaushik et al 2014). The commercial vector pBC1 with a DNA of 21.6 kbp long has been also used to obtain transgenic cattle (Yang et al 2011).…”
Section: Vectors Used In the Creation Of Transgenic Animalsmentioning
confidence: 99%
“…In 1998, Ilan et al (1998 suggested that MEC cultures could be an alternative to transgenic mice models to assess the poten-tial gene constructs for expression in the mammary gland of transgenic farm animals. Some other studies have used MEC cultures to assess the expression of the established vectors (Monzani et al 2011;Monzani et al 2013;Kaushik et al 2014;Monzani et al 2015). Although, transgenic mice can be the best model for transgenic farm animals, MEC culture is a strategy that is easier to implement than the creation of transgenic mice.…”
Section: The Evaluation Of the Constructed Vectorsmentioning
confidence: 99%
“…Plasmids permit the insertion of a DNA sequence up to 20 kb and have been used for the generation of transgenic animals. 13 The commercial pBC1 vector with 21.6 kb of DNA has been used directly or modified to generate transgenic cattle. 14 The lentiviral vectors have a restricted capacity to insert DNA, and the ideal size of genetic material to be packaged into lentiviral particles is approximately 10 kb in length.…”
Section: Vectors Used In the Generation Of Transgenic Animalsmentioning
confidence: 99%
“…29 Others studies have used MEC cultures to evaluate the expression of the vectors constructed. 13,18,19,30 Although transgenic mice may be the best model for transgenic farm animals, MEC culture is a strategy that is easier to execute than the generation of transgenic mice and shows certain advantages, such as a lower cost and an elimination of the necessity for a vivarium to produce and house transgenic mice.…”
Section: Vectors Used In the Generation Of Transgenic Animalsmentioning
confidence: 99%
“…Meantime, the cell line is also used for the study of synthesis of milk fat (Harvatine, Boisclair, & Bauman, 2014;Liang et al, 2014) and milk protein (Ball, Friis, Schoenenberger, Doppler, & Groner, 1988). Furthermore, it has been used to produce recombinant proteins by transferring exogenous gene (Kaushik et al, 2014). In addition, it can be transformed into immortalized cell line by introducing immortalized gene (Chen et al, 2016;Sun et al, 2009).…”
mentioning
confidence: 99%